Influence of Line Spacing on the Performance of Indigenous Maize Variety (Mahinda). Case Study Kabale District - Anaclet Nasasira (Uganda Christian University, 2025)
The study aimed and finding out the impact of line spacing on the performance of an indigenous maize variety (Mahinda) in Kabale District, Uganda. The trial was established BISHOP BARAHAM UNIVERSITY. The field experiment was conducted using a Randomized Complete Block Design (RCBD) with three treatments: T1-30cmx50cm, T2-60cmx30cm, T3-70cmx30cm spacing. Each treatment was replicated three times. Data were collected on plant height, number of leaves, dry and wet matter of plant plus cob size depending on different line spacing. Statistical analysis was performed using frequencies and correlation analysis to determine the significance level of differences among treatments. Additionally, a cost-benefit analysis was conducted to evaluate the profitability of spacing. It was conducted to optimize yield and improve productivity of a local maize variety that has been in kigezi for a long period of time by subjecting it to different line spacing. Data was collected on plant height, ear length, number of cobs per plant, and overall yield were measured and analyzed. The findings indicated that optimal line spacing increases production of Mahinda maize variety with a spacing of 60cmx30cm spacing giving a higher production rate. Therefore, this study suggests that Mahinda maize's productivity be boosted by using an ideal line spacing of 60 cm by 30 cm. This will increase food security and provide local farmers with more revenue. This study offers useful advice for smallholder farmers in Kabale District and emphasizes the significance of customized agronomic methods for native crop varieties.